In Search of Dotless Kropki Puzzle Solution - Andri Purnama Ramadan (LPPM Institut Teknologi Sepuluh Nopember, 2024)
Searching all possible solution and finding the minimum number of clues to make uniquely solvable puzzle always been a natural question for puzzle enthusiast. However, the attempt usually provide that as difficult task. In this paper, we attempt to search the solution of Kropki puzzle without dot clues given with graph theory approach, which resulted in a conjectures involving the planarity of graph and cyclicity of latin square.